ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT UNTUK MENGUKUR PENGARUH KEMAMPULABAAN TERHADAP PERTUMBUHAN PENJUALAN (Studi Kasus pada PT. Tjiwi Kimia dan PT. Indah Kiat Pulp & Paper Tbk.) - Fauzi, Rizki Ahmad (STIE Binaniaga, 2011)
Profitability is the ability to create profit in the company, the prifitability can kniw by anayzing elements such as analysis the Operating Profit Margin (OPM), Return On Assets (ROA) and Return On Equity (ROE). Sales growth is a trend or movement from the company activities from sale of each period. The purpose of this research is to determine: 1. To determine the influence sales growth through rasio analysis? 2. To determine a company’s financial condition through ratio analysis? 3. To determine the relationship between the ratio of sales growth and profitability ratio? Research conduction from 2003 to 2007, by taking sampled of two paper companies, namely : PT. Tjiwi Kimia Tbk, and PT. Indah Kiat Pulp & Paper Tbk Based on the results of data processing, it can be concluded that the PT. Tjiwi Kimia Tbk., in terms of sales growh ratio,PT. Tjiwi Kimia for 2003 to 2007 produced a positive trend ratio is an average of 8,42 percent. The profitability level of of PT. Tjiwi Kimia Tbk, for the year 2003 to 2007, which is seen from the company’s ability to produce the OPM (Operating Profit Margin) increased overall trend, an average of 17,9 percent, while the terms of return on equity fierm are able produces an average of 3,4 percent, and the ability in terms of return on assets decreased tendency of companies an average of 0,5 percent.Based on the correlation of the PT. Tjiwi kimia Tbk has a relationship to the operating profit margin (OPM) of 0,495 percent (positive, do not approach 1). This means that that the growth rate has a weak relationship to the operating profit marginWhile in PT. Indah Kiat Pulp & Paper Tbk, in terms of sales growth rate average of 8.94 percent, the level of profitability from 2003 to 2007, namely in terms of OPM (Operating Profit Margin) increased the overall trend is an average of 16 , 24 per cent, while for the ability in terms of ROE in the year is between 2003 to 2007 the overall trend of declining average of 0.61 percent, and for the profitability of companies in terms of ROA is also experiencing a declining trend that is an average of 1, 87 per cent. sales growth rate relationship with the operatingprofit margin (OPM) has a correlation of 0.637 percent (positive, approaching 1). This means that the growth rate has a strong relationship with the Operating Profit Margin The result ot the evalution in the study states that overall PT. Tjiwi Kimia Tbk hal a level of profitability that is better than PT. Indah Kiat Pulp & Paper Tbk, although the company has lost sales growth ratio of PT. Indah KiatKeyword: the ratio of sales growth, profitability